The perfection and self-sufficiency of the Qurʾān in the law of inheritance (part two) - Tahir, Ibrahim Nuhu (International Islamic University Malaysia, 2015)
This paper addresses the law of inheritance as detailed in the Qurʾān. It deals with the method used by the Qurʾān in this regard. It is so comprehensive in such a way that not a single person among the heirs of the deceased is left out (with the exception of the grandmother) even though the āyāt that tackled the issue are not more than four āyāt. This attitude itself indicates the great important position held by this knowledge. It is about a system that Allah took complete responsibility of its explanation in detail. This is different from the norm, whereby Allah gives the general ruling and its details or explanation will be given by the Prophet (ṣal-Allāhu ʿalayhi wa sallam). Failure to put the shares of the estate in their proper position can lead to serious disputes among family members which can lead to cutting of ties between family members. This is contrary to Islam which deems family unity and integration as essential, Allah the Almighty has taken the said responsibility of explaining it in detail to the Ummah. The paper aims to expose the beauty of the concise information about inheritance mentioned in the Qurʾān. This will be done solely through reliance on the Qurʾān and other sources which support the Qurʾān. This is the second part of two articles. Part One discusses the first type of inheritance (Farʾḍ), and Part Two discusses the second type of inheritance (Taʿṣīb). In this article, each set of conditions that qualify an heir to inherit a fixed share is accompanied by a table that illustrates their application.